2023
DOI: 10.1136/bmjopen-2022-065494
|View full text |Cite
|
Sign up to set email alerts
|

Virtually the same? Examining the impact of the COVID-19 related shift to virtual lung cancer multidisciplinary team meetings in the UK National Health Service: a mixed methods study

Abstract: ObjectivesTo evaluate the impact of the shift to virtual lung cancer multidisciplinary team meetings (MDTMs) in response to the COVID-19 pandemic, specifically in relation to the magnitude of information technology (IT) issues and distractions and MDT members’/managers’ perceptions and experiences of this shift.DesignA mixed methods study comprising real-time observations of IT issues/distractions within virtual MDTM case discussions held between April and July 2021 and qualitative data from interviews/surveys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…The number of studies at each stage of the screening process is shown in Fig 1 . Study designs of included studies were mostly observational cross-sectional studies (n = 15) [7,[17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Other study designs were retrospective review of records with a cross-sectional survey (n = 12) [5,[31][32][33][34][35][36][37][38][39][40][41], meeting observations with cross-sectional survey (n = 1) [42], mixedmethod design (n = 3) [43][44][45], embedded study design (n = 1) [46], randomized controlled trials (n = 2) [47,48], descriptive qualitative synthesis using free-text cross-sectional surveys (n = 1) [49], and an anthropological analysis (n = 1) [50]. A detailed summary of study characteristics is shown in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…The number of studies at each stage of the screening process is shown in Fig 1 . Study designs of included studies were mostly observational cross-sectional studies (n = 15) [7,[17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Other study designs were retrospective review of records with a cross-sectional survey (n = 12) [5,[31][32][33][34][35][36][37][38][39][40][41], meeting observations with cross-sectional survey (n = 1) [42], mixedmethod design (n = 3) [43][44][45], embedded study design (n = 1) [46], randomized controlled trials (n = 2) [47,48], descriptive qualitative synthesis using free-text cross-sectional surveys (n = 1) [49], and an anthropological analysis (n = 1) [50]. A detailed summary of study characteristics is shown in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…One study was published in 1999 [5]. Most studies had populations from VMDTMs based in the United States of America (n = 10) [5,18,21,25,26,33,35,37,38,46], followed by the United Kingdom (n = 8) [7,17,22,23,43,44,47,48]. The distribution of these studies is described in the S5 File.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations